Hybrid Soft Computing Approaches Research and Applications - Bhattacharyya, Siddhartha; Dutta, Paramartha; Chakraborty, Susanta; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book provides a platform for dealing with the flaws and failings of the soft computing paradigm through different manifestations. The different chapters highlight the necessity of the hybrid soft computing methodology in general with emphasis on several application perspectives in particular. Typical examples include (a) Study of Economic Load Dispatch by Various Hybrid Optimization Techniques, (b) An Application of Color Magnetic Resonance Brain Image Segmentation by ParaOptiMUSIG activation Function, (c) Hybrid Rough-PSO Approach in Remote Sensing Imagery Analysis,  (d) A Study and Analysis of Hybrid Intelligent Techniques for Breast Cancer Detection using Breast Thermograms, and (e) Hybridization of 2D-3D Images for Human Face Recognition. The elaborate findings of the chapters enhance the exhibition of the hybrid soft computing paradigm in the field of intelligent computing.
Keywords: Computational intelligence; Artificial intelligence; Software engineering; Computational Intelligence; Artificial Intelligence; Software Engineering